Canto coral: uma proposta para o ensino médio - Leandro Silva (2020)
In this article, I present the Choral Singing as an articulating and mediating element of a proposal for teaching music for the classes of the subject Art in High School. The study started based on the observation of didactic proposals made in the context of Art classes, taught in a Minas Gerais state school located in the municipality of Betim. In order to facilitate the experiences of singing in the classroom, canons were used. In this musical form, it is possible to identify characteristics that favor the learning of Choral Singing in a process of imitating vocal melodies in an accessible and meaningful way. For the development of this work, authors were observed who dialogue with themes of musical education, choral singing, adolescence and artistic experience, in addition to the observance of normative documents, such as laws and curricular guidelines for this stage of Basic Education. Based on this experience, I opted for the creation and elaboration of a pedagogical proposal directed to Art Teachers, which contributes to the process of teaching / learning of the language of music and, in the same way, is practicable in the curricular activities of High School.